2001
DOI: 10.1159/000046042
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Peritoneal Mesothelial Cell Cytology and Peritoneal Histopathology with Respect to Prognosis in Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: Background: Sclerosing encapsulating peritonitis (SEP) is a serious complication seen in patients on long-term continuous ambulatory peritoneal dialysis (CAPD). We have previously reported that mesothelial cells in effluent dialysate significantly increased in size as the duration of CAPD progressed. In this study, we investigated the relationship between mesothelial cytology, histopathology of the peritoneum, and clinical outcomes of 34 CAPD patients. Methods: When peritoneal dialysis catheters were inserted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Steroids have been shown to aid in the recuperation of the digestive tract function in various ways and to have an effect on the prognosis (11). Many studies have demonstrated the usefulness of steroids in stage 1 (pre-EPS period) and 2 (inflammation period) EPS (5,12). In the present case, after 21 days of steroid therapy, the CA125 level in the dialysate increased, whereas the IL-6 in the dialysate declined.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Steroids have been shown to aid in the recuperation of the digestive tract function in various ways and to have an effect on the prognosis (11). Many studies have demonstrated the usefulness of steroids in stage 1 (pre-EPS period) and 2 (inflammation period) EPS (5,12). In the present case, after 21 days of steroid therapy, the CA125 level in the dialysate increased, whereas the IL-6 in the dialysate declined.…”
Section: Discussionmentioning
confidence: 45%
“…Although there is still no clear evidence, peritoneal lavage is considered to be a risk factor for EPS, as many EPS cases have occurred after discontinuing PD (7,(12)(13)(14). Many recent articles have reported the importance of peritoneal lavage, recommending the procedure for six months or more following the discontinuation of PD (5,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic significance of hypertrophic mesothelial cells has been assessed in peritoneal effluent in humans but also in ex vivo human peritoneal cell cultures (Bajo et al, 2004). Although the presence of hypertrophic mesothelial cells in peritoneal effluent has been considered a marker for peritoneal sclerosis (Yamamoto et al, 1998), other authors have found no remarkable functional abnormalities suggestive of severe peritoneal damage (Izumotani et al, 2001). However, Bajo et al (2004) conclude that the presence of hypertrophic mesothelial cells is not necessarily a marker of sclerosing peritonitis and that such cells may be observed in cultures from new peritoneal effluent patients with no peritoneal function abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant epithelial cells of the epithelial and mixed types often develop in the coelomic fluid. MM from the coelomic fluid is morphologically similar to reactive mesothelium (RM) which develops under pathological conditions, such as infectious diseases, liver diseases (e.g., cirrhosis and hepatitis), peritoneal dialysis, chronic inflammation, tumors, chemotherapy, and radiation therapy [3,4,5,6,7,8], precluding preoperative discrimination [3,9,10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%